PENGARUH KEMANDIRIAN BELAJAR TERHADAP GAYA BELAJAR DAN PRESTASI BELAJAR WARGA BELAJAR PENDIDIKAN KESETARAAN PAKET C DI PKBM TUNAS MEKAR - Dian Nur' Aini; Amin Yusuf (STKIP Pesisir Selatan, 2026)
This study aims to determine the effect of learning independence on learning achievement and learning styles of students enrolled in the Package C Equivalency Education program at PKBM Tunas Mekar. This study uses a quantitative approach with a correlational design. The research subjects involved 58 Package C students. Data were collected through questionnaires and documentation, then analyzed using Multivariate Analysis of Variance (MANOVA) and linear regression. The results show that learning independence has a significant effect on the learning achievement of students. However, learning independence does not have a direct effect on learning styles. Overall, learning independence plays a role in supporting the smoothness and effectiveness of the learning process in equivalency education. The novelty of this study lies in its empirical study of learning independence in non-formal education, particularly in the Package C Equivalency Education program at PKBM. The findings of this study are expected to contribute to the development of learning that encourages the improvement of learning independence among students.